Weather influence in yild and quality coffee produced in South Minas Gerais region - Martins, Everton; Aparecido, Lucas Eduardo de Oliveira; Santos, Lucas Paulino S.; Mendonça, José Marcos Angélico de; Souza, Paulo Sergio de (Coffee Science - ISSN 1984-3909, 2015)
Coffee is one of the main Brazilian export products and few studies dealing the climate influence on the yield and quality of coffee are found. This study aimed this word evaluate the climatic influence on yield and quality of coffee produced in crops with and without irrigation at different ages in southern Minas Gerais. The treatments consisted of the combination of ages of crops (2, 3 and 8 years) and water irrigation (with and without irrigation), totaling 6 treatments. The experiment was conducted in randomized blocks in the agricultural year 2014 in Muzambinho, Minas Gerais, Brazil. We evaluated the components of yield and quality of the coffee. The weather conditions during the year 2014 were atypical for the region. The coffee crop under rainfed conditions with 2 years has shown greater number of defects and fruit floats and lower density and grain yield. The hydric deficit and the air temperature were the meteorological elements with the greatest influence on yield of coffee. The weather conditions atypical not affect the quality of beverage and granulometric characteristics of coffee crops.